Tuoris: A middleware for visualizing dynamic graphics in scalable resolution display environments - Martínez, Víctor; Fernando, Senaka; Molina-Solana, Miguel; Guo, Yike (Future generation computer systems, 2020)
In the era of big data, large-scale information visualization has become an important challenge. Scalable resolution display environments (SRDEs) have emerged as a technological solution for building high-resolution display systems by tiling lower resolution screens. These systems bring serious advantages, including lower construction cost and better maintainability compared to other alternatives. However, they require specialized software but also purpose-built content to suit the inherently complex underlying systems. This creates several challenges when designing visualizations for big data, such that can be reused across several SRDEs of varying dimensions. This is not yet a common practice but is becoming increasingly popular among those who engage in collaborative visual analytics in data observatories. In this paper, we define three key requirements for systems suitable for such environments, point out limitations of existing frameworks, and introduce Tuoris, a novel open-source middleware for visualizing dynamic graphics in SRDEs. Tuoris manages the complexity of distributing and synchronizing the information among different components of the system, eliminating the need for purpose-built content. This makes it possible for users to seamlessly port existing graphical content developed using standard web technologies, and simplifies the process of developing advanced, dynamic and interactive web applications for large-scale information visualization. Tuoris is designed to work with Scalable Vector Graphics (SVG), reducing bandwidth consumption and achieving high frame rates in visualizations with dynamic animations. It scales independent of the display wall resolution and contrasts with other frameworks that transmit visual information as blocks of images. •Definition 3 key software systems suitable for displaying data on SRDEs.•Review of existing visualization frameworks for SRDEs, pointing out limitations.•Description of TUORIS: its components, design and implementation.•Display previously created SVGs in a SRDE with no modification or performance penalty.•Evaluation of TUORIS’ performance and scalability on several scenarios.